2008
DOI: 10.1186/1471-2407-8-378
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism +17 C/G in Matrix Metalloprotease MMP8 decreases lung cancer risk

Abstract: Background: Matrix metalloproteases (MMPs) constitute a family of enzymes capable of degrading different components of the extracellular matrix and are implicated in the invasion of tumor cells through the basement membrane. Polymorphisms in MMP genes may result in changes in the expression of MMPs being associated with the development and progression of cancer. We have investigated the association between three polymorphisms (-1607 1G/2G, +17 C/G and -77 A/G) in the human collagenases MMP1, MMP8 and MMP13 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…From the molecular viewpoint, MMP-8 might increase cell adhesion by rearrangement of cytoskeleton actin, thus decreasing cell invasion (32). However, there were few epidemiological studies investigating the role of MMP-8 polymorphisms in the susceptibility of cancers (33). In 2008, the G variant allele at MMP-8 +17 C/G was found to be associated with a decreased risk of developing lung cancer (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the molecular viewpoint, MMP-8 might increase cell adhesion by rearrangement of cytoskeleton actin, thus decreasing cell invasion (32). However, there were few epidemiological studies investigating the role of MMP-8 polymorphisms in the susceptibility of cancers (33). In 2008, the G variant allele at MMP-8 +17 C/G was found to be associated with a decreased risk of developing lung cancer (33).…”
Section: Discussionmentioning
confidence: 99%
“…However, there were few epidemiological studies investigating the role of MMP-8 polymorphisms in the susceptibility of cancers (33). In 2008, the G variant allele at MMP-8 +17 C/G was found to be associated with a decreased risk of developing lung cancer (33). Thereafter in the present study, we firstly focused on the genotypes of MMP-8 polymorphisms and assessed whether there was an association between the genotypes of the promoter region of MMP-8 (-799C/T) and two nonsynonymous polymorphisms (Val436Ala and Lys460Thr) with pterygium risk.…”
Section: Discussionmentioning
confidence: 99%
“…From the molecular viewpoint, MMP-8 might increase cell adhesion by rearrangement of cytoskeleton actin, thus decreasing cell invasion (33). However, there were few epidemiological studies investigating the role of polymorphisms in MMP-8 to the susceptibility of cancers (34). In 2008, the G variant allele at MMP-8 +17 C/G was found to be associated with a decreased risk of developing lung cancer, while there was no contribution of the particular polymorphism to the overall survival rates for the lung cancer patients (35).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the promoter comprising the 2G allele has significantly greater transcriptional activity compared with the 1G promoter, because the 2G allele creates a transcription factor binding site and increases transcription capacity (Su et al, 2006;Chen et al, 2012). A few studies on the association between this polymorphism and lung cancer susceptibility have been published, but those results were inconsistent and inconclusive (Zhu et al, 2001;Su et al, 2006;Gonzalez-Arriaga et al, 2008;Hart et al, 2011). To further evaluate the role of the MMP1 rs1799750 polymorphism in the development of lung cancer, we conducted a meta-analysis to investigate the association between this polymorphism and the occurrence of lung cancer.…”
Section: Introductionmentioning
confidence: 99%